PROBLEMATIKA KREDIT MACET DENGAN JAMINAN YANG TIDAK DIDAFTARKAN DALAM BENTUK FIDUSIA PADA BANK PERKREDITAN RAKYAT SAMARINDA - Steven Bun (Journal of Law ( Jurnal Ilmu Hukum ), 2013)
ABSTRACTFinancing is one of the economic activities that drive economic market system proved to be one important aspect of the business continuity for the majority of the Indonesian people. One form of financing is credit, and that becomes the container for credit itself is one of his bank. Extension of credit by the banks themselves should be based on sound principles and prudence so as not to harm the bank as a creditor, debtor and communities that have holdings in the bank. In the journey of obtaining loans from banks in needed guarantees as protection to the creditor that the debtor will carry out its obligations. One form of collateral is fiduciary, the fiduciary institution, the relationship between the debtor and the creditor based on trust. Fiduciary insurance will be recorded in the Register of Fiduciary, Fiduciary Registration Office and will be published in the form of certificates of proof People's Bank lending in Samarinda is one example of cooperative banks as creditors shaped by giving loans to his debtor clients. In its consensus agreement, BPR require to register object credit in fiduciary institutions, fiduciary itself actually has many benefits for both parties if either party so injured that promises the other party can directly execute their fiduciary bail in court without waiting for the process time consuming. In practice it turns out BPR in Samarinda did not object underwriting guarantee to a fiduciary institution as some factors that could inhibit assessed their working existence.Keywords: Fidusia